Manipulating Crystallographic Orientation of Zinc Deposition for Dendrite‐free Zinc Ion Batteries. Issue 29 (10th June 2021) - Cao, Jin; Zhang, Dongdong; Gu, Chao; Wang, Xiao; Wang, Shanmin; Zhang, Xinyu; Qin, Jiaqian; Wu, Zhong‐Shuai
Abstract: The dendrite issues associated with zinc anode lead to safety hazards and sluggish reaction kinetics, and largely restrain widespread application of aqueous zinc ion batteries (ZIBs). Herein, a functional separator composed of cellulose nanofibers and graphene oxide (CG) is developed for dendrite‐free and exceptionally stable ZIBs, realized by uniform hexagonal zinc deposits with manipulated crystallographic orientation (002) plane. This CG separator with negative surface charges and abundant zincophilic‐O groups ensures the strong interaction between the separator and zinc species, simultaneously inducing Zn(002) deposition due to the low mismatch between (002)Zn and (002)GO, thus initiating the preferential orientation of the zinc growth along the horizontal direction due to strong Zn binding ability, and uniform interfacial charge of Zn(002) deposition. Furthermore, the CG separator can effectively promote the uniform nucleation of Zn 2+ and eliminate side effects. Accordingly, extremely low polarization of 58 mV at 0.5 mA cm −2, and ultralong cycle life over 1750 h at 2 mA cm −2 and 400 h at 20 mA cm −2 are achieved for the zinc anode. Notably, the CG separator significantly boosts rate capability and cyclability of coin‐type full batteries (Zn|| Zn(CF3 SO3 )2 || V2 O5, Zn|| ZnSO4 + MnSO4 ||MnO2 /graphite) and a flexible soft‐packaged battery (Zn|| MnO2 ). Therefore, this work introduces a sustainability consideration in to the design of separators for constructing dendrite‐free ZIBs. Abstract : A functional separator composited by cellulose nanofibers and graphene oxide (CG separator) is developed for dendrite‐free and exceptionally stable zinc‐ion batterie, realized by uniform hexagonal zinc deposits with manipulated crystallographic orientation (002) plane in the Zn anode.